A ambiguidade entre o vivido e o criado: intermidialidade, memória e metaficção em Dor e glória, de Pedro Almodóvar - Fernandes, Marcelo de Lima (2023)
Pain and glory, a 2019 film by spanish director Pedro Almodóvar, follows distinct moments in the life of Salvador Mallo (Antonio Banderas), a movie director. The main aim of this work is, using the theoretical categories of intermediality (MOSER, 2006; CLÜVER, 2006; 2012; RAJEWSKY, 2012, 2020), metafiction (WAUGH, 1984; HUTCHEON, 1991) and memory (BERGSON, 1999; HALBWACHS, 2006), to analyze how, in Pain and glory, fiction has a prevailing role in the journey of the protagonist and other characters in the movie. Therefore we base our discussions in the context of self-writing (LEJEUNE, 2008; DOUBROVSKY, 2011; FAEDRICH, 2014; COLONNA, 2014) in order to understand how these theoretical strategies induce a state of ambiguity between fiction and reality in the film’s narrative. We also use the ideas of concrete, or everyday, ideology (VOLÓCHINOV, 2018) and the policy of the amateur (RANCIÈRE, 2012) to verify in which ways fiction can permeate everyday life, as suggested by Pain and glory. In our analysis, we found that Almodóvar’s film uses distinct strategies and narrative tools - as the dialogues with other narrative players from different media, such as Fernando Pessoa’s Book of disquiet and Federico Fellini’s 8 ½ - to lift the distinction between fiction and reality within the movie’s diegesis, raising questions about the materiality that fiction acquires on everyday life, the (in)distinction between memory and creation and the artist’s role on the construction of multiple possibilities of being in the world.